2011
DOI: 10.1104/pp.111.176248
|View full text |Cite
|
Sign up to set email alerts
|

EOBII Controls Flower Opening by Functioning as a General Transcriptomic Switch    

Abstract: R2R3-MYB transcription factors (TFs) are involved in diverse aspects of plant biology. Recently an R2R3-MYB was identified in Petunia x hybrida line P720 to have a role in the transcriptional regulation of floral volatile production. We propose a more foundational role for the R2R3-MYB TF EMISSION OF BENZENOIDS II (EOBII). The homolog of EOBII was isolated and characterized from P. x hybrida 'Mitchell Diploid' (MD) and Nicotiana attenuata. For both MD and N. attenuata, EOBII transcript accumulates to high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Silencing the expression of the MYB305 homolog EOBII in petunia (Petunia hybrida) results in floral corollas that fail to enter anthesis, whereas in MYB305-silenced N. attenuata plants, flowers abscised prematurely (Colquhoun et al, 2011). However, while the accumulation of MYB305 transcripts was also delayed in dissected corolla tissues of ir-coi1 and ir-aoc flowers, maximal levels at the onset of anthesis were similar to those of wildtype corollas at anthesis ( Figure 3B).…”
Section: The Duet Of Ja-ile and Coi1 Determines Traits For Pollinatormentioning
confidence: 95%
See 1 more Smart Citation
“…Silencing the expression of the MYB305 homolog EOBII in petunia (Petunia hybrida) results in floral corollas that fail to enter anthesis, whereas in MYB305-silenced N. attenuata plants, flowers abscised prematurely (Colquhoun et al, 2011). However, while the accumulation of MYB305 transcripts was also delayed in dissected corolla tissues of ir-coi1 and ir-aoc flowers, maximal levels at the onset of anthesis were similar to those of wildtype corollas at anthesis ( Figure 3B).…”
Section: The Duet Of Ja-ile and Coi1 Determines Traits For Pollinatormentioning
confidence: 95%
“…[See online article for color version of this figure. ] quantified corolla transcript levels of central JA biosynthesis genes from 1 DAP until anthesis ( Figures 3A and 3B). We additionally measured the transcript levels of JAZd, a recently identified transcriptional repressor of JA accumulation in complete N. attenuata flowers (Oh et al, 2013), and Na-MYB305, the N. attenuata homolog of Arabidopsis MYB21, a transcription factor in various plant species known for its role in floral development (Liu et al, 2009;Colquhoun et al, 2011;Reeves et al, 2012). Expression of the N. attenuata JA biosynthesis transcripts AOS (Kallenbach et al, 2012) and THREONINE DEAMINASE (TD) (Kang et al, 2006) peaked in wild-type, ir-aoc, and ir-coi1 corollas at 1 DAP and decreased in conjunction with corolla expansion ( Figure 3B).…”
Section: Transcriptional Activation Of Ja Biosynthesis Precedes Ja-ilmentioning
confidence: 99%
“…EMISSION OF BENZENOIDS II (EOBII), similar to PAP1 and in contrast with ODO1, has been shown to regulate the transcription of both shikimate pathway genes and genes directly involved in the biosynthesis of phenylpropanoid volatiles (Verdonk et al, 2005;Dare et al, 2008;Ben Zvi et al, 2008;Spitzer-Rimon et al, 2010;Zvi et al, 2012). While it has been recently suggested that EOBII may also have activities outside the scope of floral scent production (Colquhoun et al, 2011b), the epistatic relations between EOBII and ODO1 have been confirmed: EOBII binds directly to ODO1's upstream regulatory sequence and transcriptionally activates its expression (Van Moerkercke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…19) The EOBII homolog isolated from Petunia x hybrida "Mitchell Diploid" and Nicotiana attenuate is involved in the sexual reproduction process of flower opening. 20) There has been a rapid progress in elucidating the biosynthetic pathways, enzymes, and genes involved in the formation of plant volatile compounds, which has enabled the investigation of their physiology and function at the molecular and biochemical basis. 21) Roses are called the "queen of scents" because of the attractive and sweet odor that they emit.…”
mentioning
confidence: 99%